Influence of plasma condition on carbon nanotube growth by rf-PECVD - Man, Y. H.; Li, Z. C.; Zhang, Z. J. (Nano-Micro Letters, 2010)
Carbon nanotubes (CNTs) have been synthesized from Ar-CH4 mixtures using rf-plasma enhanced chemical vapor deposition (rf-PECVD) at 500°C. Reduction gases such as H2 and NH3 were found unnecessary for carbon nanotube formation compared to thermal CVD. The relationship between the growth of CNTs and the plasma condition in PECVD has been investigated by in situ self bias measurement. Plasma conditions were controlled by changing the interelectrode distance, rf power and the applied substrate negative bias. By increasing the interelectrode distance and rf power, the spatial density of CNTs was on a rise as a result of the increase in ions density and self bias. As the applied substrate negative bias increased, the spatial density of CNTs decreased possibly due to the positive ions over bombarding effect.